Transformation of Islamic Religious Education in Building the Character of the Millennial Generation - Sodikin Sodikin; Martoyo Martoyo (JISEI: Journal of Islamic Studies and Educational Innovation, 2026)
Millennial generation grows amidst rapid technological advancement and globalization that threaten their moral stability and Islamic identity. Islamic Religious Education (PAI) is required to transform in order to serve as both a shield and a guide in character formation for this generation. This study aims to examine the transformation process of PAI encompassing curriculum, methodology, and technology dimensions in building the character of the millennial generation to be noble, tolerant, and imbued with moderate Islamic values. The research employs a qualitative approach using library research technique through content analysis of relevant primary and secondary sources published between 2018 and 2024. Results: The findings indicate that effective PAI transformation encompasses integration of digital literacy in learning, application of contextual and active approaches, and cultivation of religious moderation values. These three aspects are proven to enhance student engagement and strengthen their Islamic character in the digital era. PAI transformation is not merely a technical renewal, but a strategic effort in responding to the demands of the times while adhering to universal Islamic values. The synergy among educators, educational institutions, families, and technology is the key to successfully building a generation of millennials with strong character.